THE ROLE OF POLYTABLETS (POLYPILL) IN THE TREATMENT OF CHRONIC CARDIOVASCULAR DISEASES - Абрамов, Николай Владимирович; Кашталап, Василий Васильевич; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2024)
This review focuses on the use of fixed combinations of drugs affecting cardiovascular disease risk factors. The main obstacle to adherence to the treatment of cardiovascular diseases is polypragmasy and unfavorable drug interactions, especially in elderly patients. Recent information on the use of polypills in the treatment of cardiovascular disease and their effect on adherence to treatment is reviewed and summarized.